Physicochemical and tribological analysis of chemically modified microalgae oil blends for Malaysian conditions / Cheah Mei Yee - Cheah , Mei Yee (2019)
Many health and environmental issues like skin and respiratory disease due to groundwater contamination, greenhouse gasses, and toxic smog have been linked to the usage of fossil-based lubricant and fuel. This growing demand for greener alternatives has led scientist to microalgae, an ancient organism with more than 100,000 species. In order to bioprospecting local microalgae species that will eradicate the issue of alien species invasion of local ecosystem, we have identified and isolated five local freshwater microalgae species. Their suitability (including two purchased species) for biolubricant production were assessed from the growth, biomass productivity and lipid composition aspects. The oil extraction process, chemical modification and the physicochemical properties of the selected species were investigated, followed by the tribological performance evaluation as a biolubricant and as an additive in diesel and in a commercial full synthetic lubricant (FFL). It was found that Chlorella sp. and Ankistrodesmus sp. exhibited comparable growth rate and lipid yield (higher than other tested species). However, Chlorella sp. was selected over Ankistrodesmus sp. due to its lipid composition as this species contained higher amount of long carbon chain fatty acids and unsaturation. The higher amount of long carbon chain fatty acids and unsaturation are found to produce thicker lubricating film and exhibit better cold weather performance, two important properties for biolubricant application. The lipid yield has been successfully increased by changing the extraction solvent from petroleum ether to chloroform: methanol (2:1). Additionally, chemical modification can be used to reduce the acidity of the extracted oil as free fatty acids were converted into esters. Results indicate that chemically modified microalgae oil (MMO) can be used as friction modifier. We observed a decline in friction coefficient (COF) when blending percentage is increased compared with pure polyalphaolefin (PAO) (used as base-oil) sample, though the further increase in blending percentage (above 10%) ceased to cause any further improvement on the COF. On the aspect of wear prevention and performance in extreme pressure condition, MMO-10 showed notable results that were comparable to a FFL. It exhibited a load-wear index (an important load carrying parameter for an EP additive) that was similar to that of a commercial lubricant. Our analyses further revealed that MMO-10 was thermally stable and exhibited better combustion than PAO, and the oxidation stability of PAO was extended to more than 24 folds with MMO addition. The presence of oxygen-containing compounds and natural antioxidants would be the reasons for such observations. When MMO was used as additives in diesel, significant wear reduction was observed compared with pure diesel. However, no further improvement on the wear were observed with the increase of MMO above 8%. Further, the fluctuations of COF and wear with the increase of MMO-10 percentage indicates that the interactions between MMO-10 and FFL were more complex though blending at 2% and below enhances the wear and COF of pure FFL. In conclusion, chemically modified microalgae oil (particularly, MMO-10) is an effective friction modifier and has shown great potential as an anti-wear and EP additives for lubricant.